STUDENTS AND TEACHERS’ ANXIETY LEVELS IN LEARNING ENGLISH DURING THE EMERGENCY REMOTE TEACHING IN INDONESIA - Bidari, Ni Putu Intan; Santosa, Made Hery; Mahendrayana, Gede (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
The aim of this study was to investigate the anxiety level of the students and teachers in teaching and learning English during the emergency remote teaching in Indonesia. This quantitative study used Foreign Language Classroom Anxiety Scale (FLCAS) for collecting the students and teachers’ anxiety levels during the pandemic situation. The participants of the study were 199 students and 3 English teachers in a senior high school in Indonesia. The study found that the students’ anxiety level was moderate (3.04). It indicated that the students were not afraid but also did not fully enjoy learning English with the new learning system. Meanwhile, the teachers’ anxiety was categorized as low anxiety (2.2), meaning that the teachers enjoyed and did not worry about teaching English during the emergency remote teaching. In conclusion, new learning environment for EFL, the students and teachers had different anxiety levels with students needed more attentions for better assistance of optimal learning quality. The results of this study were expected to give beneficial information for the students and teachers that learn and teach English during the pandemic situation.